A Teenager With Rash and Fever: Juvenile Systemic Lupus Erythematosus or Kawasaki Disease? - Saez-de-Ocariz, Marimar; Pecero-Hidalgo, María José; Rivas-Larrauri, Francisco; García-Domínguez, Miguel; Venegas-Montoya, Edna; Garrido-García, Martín; Yamazaki-Nakashimada, Marco Antonio (Frontiers in Pediatrics, 2020)
Rationale. Kawasaki disease (KD) is an acute vasculitis of small and medium vessels; whereas systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease. Their presentation is varied and not always straightforward, leading to misdiagnosis. There have been case reports of lupus onset mimicking KD and KD presenting as lupus-like. Coexistence of both diseases is also possible. Patient concerns. We present three adolescents, one with fever, rash, arthritis, nephritis, lymphopenia and coronary aneurysms, a second patient with rash, fever, aseptic meningitis and seizures, and a third patient with fever, rash and pleural effusion. Diagnoses: The first patient was finally diagnosed with SLE and KD, the second patient initially diagnosed as KD but eventually SLE and the third patient was diagnosed at onset as lupus but finally diagnosed as KD. Interventions. The first patient was treated with IVIG, corticosteroids, aspirin, coumadin and mycophenolate mofetil. The second patient was treated with IVIG, corticosteroids and methotrexate and the third patient with IVIG, aspirin and corticosteroids. Lessons: Both diseases may mimic each other´s clinical presentation. KD in adolescence presents with atypical signs, incomplete presentation, and develop coronary complications more commonly. An adolescent with fever and rash should include KD and SLE in the differential diagnosis.